TERTIARY INSTITUTIONS IN NIGERIA AND HUMAN MANAGEMENT STRATEGIES - Olapade , Olubunmi Olubunmi (Multi-Disciplinary Research and Development Journals Int'l, 2025)
This chapter examines human relations management strategies in Nigerian tertiary institutions, highlighting their roles in fostering institutional stability, academic excellence, and national development. Drawing on policy documents (e.g. National Policy on Education, 2013) and empirical studies from Nigerian universities and colleges, the chapter defines key concepts such as human relations management, tertiary education, and human relations management strategies. It identifies effective practices—including open communication, participatory decision-making, conflict resolution and mediation, recognition and motivation, teamwork and capacity building, welfare support, and fairness—that promote positive human relations among administrators, academic and non-academic staff, and students. The chapter also discusses major challenges undermining these strategies in the Nigerian context: inadequate funding, poor leadership styles, frequent industrial actions, administrative bureaucracy, cultural diversity, resistance to change, and weak communication structures. Finally, it proposes that institutional leadership adopt more democratic, inclusive, and well-funded human relations frameworks, backed by continuous training and transparent policy implementation, to harness human resources as strategic assets.